PENGARUH MOTIVASI DAN KOMITMEN KARYAWAN TERHADAP PRESTASI KERJA PADA PT. MARINA PUTRA INDONESIA PERWAKILAN KABUPATEN LUWU UTARA - Salju Salju; Mastia Mastia (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of research is to know and analyze the Influence of Motivation and Employee Commitment to Work Achievement At PT. Marina Putra Indonesia Representative of North Luwu Regency. The research is an explanatory research and using survey method. The research population is the employees of PT. Marina Putra Indonesia Representative of North Luwu District, which amounts to 15 people are also used as samples in research. Data analysis method used in this research is descriptive analysis and Multiple Linear Regression, where independent variable consists of motivation and Commitment of Employees while for dependent variable that is Work Achievement. The result of research by using multiple linear regression analysis shows that simultaneously (Test F) motivation and commitment variable have a significant effect on Job Performance variable, so the first hypothesis in this research which suspect that motivation and Commitment have positive and significant impact on Employee Work Achievement PT. Marina Putra Indonesia Representative of North Luwu Regency proved true. While for (t-test) from the result turn out motivation variable which have positive significant effect and have dominant influence to Work Achievement with regression coefficient value equal to 50,4%. While for the Commitment variable has a positive effect is not significant on Job Performance with the value of regression coefficient value of 7.8%. Thus the second hypothesis in this study that suspect that motivation has a dominant effect on employee performance of PT. Marina Putra Indonesia Representative of North Luwu Regency is proven true.